Reception of Ancient Plot of Odyssey in Stefan Schütz’s Play “Odysseus' Heimkehr” - A. S. Frolova (Научный диалог)
This article analyzes the distinctive features of the transformation of the plot concerning Odysseus’s return to Ithaca in Stefan Schütz’s play “Odysseus’ Heimkehr” (1972). The relevance of this study is underscored by the strategies of representation of modernity presented in the play, which are intricately linked to the reception of ancient heritage. Employing a cultural-historical method, along with receptive and mythopoetic approaches to textual analysis, the study concludes that all mythological characters in the play undergo a process of re-evaluation: the figures of Telemachus and Penelope are travestied and deheroized, while Odysseus himself is stripped of his heroic stature. The issue of identity, as it pertains to the character of Odysseus, is interpreted as one of the central themes of the play. Its exploration is structurally realized at the compositional level through the motif of recognition. Schütz’s artistic engagement with myth is assessed as being in line with the main tendencies in the reception of Antiquity within GDR dramaturgy. The play is demonstrated to possess a pronounced socio-critical orientation, reflecting on the consequences of totalitarian regimes and the mechanisms of ideological formation. This thematic exploration is embodied in the text of the drama through the metaphor of illness as a tool for controlling public consciousness.